2018
DOI: 10.1088/1367-2630/aac5ce
|View full text |Cite
|
Sign up to set email alerts
|

Paving the way for a revolution in high repetition rate laser-driven ion acceleration

Abstract: Exceptionally strong TV m −1 fields generated during the interaction of high intensity lasers with plasma targets are capable of accelerating ions to MeV energies over micron-scale distances. This offers exciting possibilities for the development of compact accelerators. It has been demonstrated that the maximum achievable ion energy scales with the laser intensity and consequently much of the work in this field has utilised lasers at the cutting edge of development with multi-J energies and short ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In this paper, we show that an ultra-intense laser–matter interaction produces a versatile, non-destructive, fast analysis technique that allows, within a single sub-ns shot, to switch from laser-driven PIXE to laser-driven XRF, or to apply both techniques simultaneously. By simply changing the atomic number (Z) of the laser interaction target, one can toggle between these techniques from shot to shot, in the same installation, within seconds or less (the delay depends on the time to move from one target to the other, currently the community is targeting repetition rates > 1 Hz 28 ). This versatility allows performing firstly a volumetric analysis (using the X-rays or a large energy spread of the protons) and then a layer-by-laser analysis (using narrow band proton energies).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we show that an ultra-intense laser–matter interaction produces a versatile, non-destructive, fast analysis technique that allows, within a single sub-ns shot, to switch from laser-driven PIXE to laser-driven XRF, or to apply both techniques simultaneously. By simply changing the atomic number (Z) of the laser interaction target, one can toggle between these techniques from shot to shot, in the same installation, within seconds or less (the delay depends on the time to move from one target to the other, currently the community is targeting repetition rates > 1 Hz 28 ). This versatility allows performing firstly a volumetric analysis (using the X-rays or a large energy spread of the protons) and then a layer-by-laser analysis (using narrow band proton energies).…”
Section: Introductionmentioning
confidence: 99%
“…Ultra-intense laser systems can potentially serve as a compact source of energetic ions. As discussed, for example, in 8,9 laser technology is maturing rapidly towards this goal.…”
Section: Introductionmentioning
confidence: 99%
“…As described in Morrison et al 19 , 5 mJ laser pulses with a peak intensity near 5 • 10 18 W cm −2 were used to accelerate protons up to 2.5 MeV in energy and at a kHz repetition rate. As discussed in a perspectives article by Palmer 9 , producing ∼2 MeV protons from a few mJ class laser system operating at a kHz repetition rate had not been achieved before.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we have shown that the combination of water microdroplets irradiated at 2 ω frequencies and probing with off-harmonic wavelengths has great potential for the investigation of laser-plasma interactions. Furthermore, the ease of droplet production, their synchronizability with the pump laser and availability at high repetition rates demonstrate that droplets are a promising target for laser-driven proton acceleration as well as for secondary radiation sources 45 .…”
Section: Discussionmentioning
confidence: 99%